Tailoring Nitrogen Species in Disk‐Like Carbon Anode Towards Superior Potassium Ion Storage. Issue 30 (3rd July 2022) - Wang, Gongrui; Wang, Wentao; He, Xiaoyue; Li, Jie; Yu, Lai; Peng, Bo; Liu, Rong; Zeng, Suyuan; Zhang, Genqiang
Abstract: Carbon materials, as promising anode candidates for K + storage due to their low cost, abundant sources, and high physicochemical stability, however, encounter limited specific capacity and unfavorable cycling stability that seriously hinder their practical applications. Herein, a feasible strategy to tailor and stabilize the nitrogen species in unique P/N co‐doped disk‐like carbon through the Sn incorporation (P/NSn –CD) is presented, which can largely enhance the specific capacity and cycling capability for K + storage. Specifically, it delivers a high specific capacity of 439.3 mAh g ‐1 at 0.1 A g ‐1 and ultra‐stable cycling capability with a capacity retention of 93.5% at 5000 mA g ‐1 over 5000 cycles for K + storage. The underlying mechanism for the superior K + storage performance is investigated by systematical experimental data combined with theoretical simulation results, which can be derived from the increased edge‐nitrogen species, improved content and stability of P/N heteroatoms, and enhanced ionic/electronic kinetics. After coupling P/NSn –CD anode with activated carbon cathode, the KIHCs can deliver a high energy density of 171.7 Wh kg ‐1 at 106.8 W kg ‐1, a superior power density (14027.0 W kg ‐1 with 31.2 Wh kg ‐1 retained), and ultra‐stable lifespan (89.7% retention after 30 K cycles with cycled at 2 A g ‐1 ). Abstract : The nitrogen species is successfully tailored and stabilized by simply incorporating in P/N co‐doped carbon with disk‐like morphology, which can act as a superior K + host with remarkable specific capacity and outstanding cycling performance.